Breast cancer survivorship in an Asian specialist centre from Malaysia: A retrospective analysis - Ahmad, Azura Rozila; Tan, Jia Shin Jessica; Manivannan, Arkonam Balasubramaniam; Wahid, Mohamed Ibrahim Abdul (Asian Journal of Medical Sciences, 2019)
Background: Real world data (RWD) is increasingly relevant in breast cancer (BCa) as it is the most frequently diagnosed cancer. Developed world has seen improved breast cancer survival, however, RWDon BCa survival in Malaysia is still lacking. Aims and Objectives: This study aims to determine characteristics and survival of BCa patients from a single institute. Materials and Methods: Retrospective analysis of 168 BCa patients who were treated with at least one treatment modality in Beacon International Specialist Centre (BISC) from 2008-2012 was conducted. Patient characteristicsand treatments received were analysed descriptively to survival outcome.Vital status was obtained from the National Registry of Birth and Death (NRD) records. Observed survival rates wereestimated by Kaplan-Meier method and difference between groups by log-rank. Results: Of 143 eligible BCa patients,28 (19.6%) died during the study period. Five-year BCa specific survival rates were 100% for Stage I and II, 79.31% for stage III and 38.89% for Stage IV disease. In the multivariate analysis, higher stage at diagnosis, triple negative breast cancer with metastases and higher grade were associated with worse survival outcomes. The overall 5-year survival rate of BCa patients in BISC from 2008-2012 compares favourably to the survival data of developed countries. Conclusion: In conclusion, the overall 5-year survival rate of BCa patients in BISC compares favourably to the survival data of developed countries, as well as to other institutions.